A Propensity-Matched Cohort Assessing Impact of a Neutralizing Monoclonal Antibody in Mild-to-Moderate Coronavirus Disease 2019. (June 2023) - Abbas, Malak; Farhat, Nada; Hammoud, Zainab; Dickey, Curtis; Shuayto, Ali; Chen, Nai-Wei; Hsaiky, Lama M; Sims, Matthew; Sengstock, David; Schramski, Joseph; Shamoon, Zafar
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoaV-2) is responsible for the coronavirus disease 2019 (COVID-19) pandemic. In randomized clinical trials, patients who were treated with the anti-spike monoclonal antibody bamlanivimab had fewer COVID-19-related hospitalizations or emergency department (ED) visits than the control group.Methods: A retrospective cohort was assembled across a multisite healthcare system between November 20, 2020 and March 31, 2021. Ambulatory COVID-19 patients treated with bamlanivimab (n = 209) were propensity score matched without replacement (1:1) to a pool of 1024 eligible control patients who received similar care without bamlanivimab. The primary endpoint was all-cause mortality or admission at 30 days. Secondary endpoints included hospitalization, critical care admission, oxygenation requirements, and infusion-related reactions. Propensity score matching (PSM) analysis was used to assess the effect of bamlanivimab infusion on the composite endpoint and secondary endpoints.Results: A total of n = 209 matched patients were included in each arm of the study. The absolute standardized difference ( stddiff ) was calculated and indicated a balance between the groups. Almost all variables had a stddiff of less than 0.10, except for respiratory rate (RR) ( stddiff  = −0.11). For the primary composite endpoint of the matched cohort, 10.1% (n = 21) of patients in the intervention group were hospitalized or deceased within 30-day postbamlanivimab infusion versus 27.8% (n = 58) in the control group (adjusted odds ratio [aOR]: 0.29, 95% confidence interval [CI]: 0.17 to 0.51, P  < .001).Conclusion: Patients with ambulatory COVID-19 who received bamlanivimab in the outpatient setting had a statistically significant reduction on the odds of admission postinfusion. Despite bamlanivimab's lack of efficacy on newer SARS-CoV-2 variants, this study demonstrates that neutralizing monoclonal antibodies can be effective against specific variants. If variant identification becomes a more accessible tool in outpatient centers or EDs, more targeted therapeutic options may be considered.